Family Clustering Based On Y-Chromosome DNA Profile Using Unweighted Pair Group Method with Arithmetic Mean - Meira Parma Dewi; Nurtami Soedarsono (UIN Sumatera Utara, 2026)
Indonesia is a diverse nation composed of numerous ethnic groups, each with distinct physical and genetic characteristics. Genetic similarities within ethnic populations can be examined through DNA profiling, particularly by analyzing Short Tandem Repeat loci. In Indonesia, DNA profiling has been widely applied in forensic identification and paternity testing. This study focuses on classifying the Javanese population into sub-tribes based on STR profile similarities using divisive hierarchical clustering. The optimal number of clusters was determined by the smallest Sum of Squared Errors (SSE), with the lowest value of 72583.12and the highest Silhouatte coeffisien value is 0.78, yielding seven sub-tribe clusters. Subsequently, these sub-tribe clusters were further classified into family clusters using Y-chromosome STR (YSTR) data, which traces paternal lineage. The clustering process employed the Unweighted Pair Group Method with Arithmetic Mean, resulting in 21 family clusters. Compared to k-means clustering, divisive clustering produced sub-tribe clusters with more balanced population sizes. The establishment of sub-tribe and family clusters enhances the efficiency of individual identification, as DNA profile matching can be performed at the cluster level rather than across the entire population. This approach provides a more systematic framework for forensic applications and victim identification, particularly in cases involving male individuals where YSTR data is critical.